Boosting Employee Performance in Indonesia Through Environment, Motivation, and Quality: Meningkatkan Kinerja Karyawan di Indonesia Melalui Lingkungan, Motivasi, dan Kualitas - Firda Oktavia Asfianto; Kumara Adji Kusuma (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of the work environment, motivation, and human resource quality on employee performance at PT Indo Lautan Makmur's vacuum department. Using a quantitative approach, data were collected from 120 employees through online questionnaires and analyzed with SPSS. Results indicate that a positive work environment, strong motivation, and high-quality human resources significantly improve employee performance. These findings suggest that enhancing these factors can effectively boost employee performance at PT Indo Lautan Makmur. Highlights: 1. Positive work environment significantly boosts employee performance.2. Motivation alone doesn't always guarantee performance improvement.3. High-quality human resources enhance employee performance. Keywords: Work environment, Motivation, Human resource quality, Employee performance, Quantitative research